PENGARUH PROFITABILITAS, LEVERAGE, KEPEMILIKAN MANAJERIAL, SALES GROWTH TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR - Marselinus, Marselinus; Sha, Thio Lie (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to determine the effect of profitability, leverage, managerial ownership, and sales growth on the dividend policy in manufacturing companies on the IDX during 2018-2020. The method used is purposive sampling with valid data as many as 32 companies. Data processing is using Eviews program version 12. The results of this show that profitability has a negative significant and leverage has a positive significant effect on dividend policy, while managerial ownership has a positive insignificant and sales growth has a negative insignificant effect on dividend policy. The implication of this research are expected to give consideration for companies to make decisions related to factors that affect dividen policy.